Traffic Impact Analysis Due to Construction of Special Eye Hospital Padang Eye Center - Wahab, Wilton; Roza, Angelalia; Ranjani, Aisyah (CIVED, 2024)
Padang Eye Center is one of the hospitals under construction on Jalan Khatib Sulaiman, Lolong Belanti, North Padang District, Padang City, West Sumatra. The construction of the hospital will certainly have an impact on traffic on Jalan Khatib Sulaiman. The purpose of conducting andalalin is to analyze the amount of travel demand that occurs at the Padang Eye Center Hospital in pre-construction, construction period, operational period, and post 5 years of construction, as well as seeing the impacts that occur and how alternative solutions are carried out. The parameters used are based on the Regulation of the Minister of Transportation of the Republic of Indonesia Number 17 of 2021 concerning the implementation of andalalin, the Indonesian Road Capacity Guidelines (PKJI) of 2023 concerning the performance of road sections and the Directorate General of Land Transportation of 1996 concerning parking. The results of the analysis, namely the existing conditions obtained a V / C ratio of 0.43 level B, the construction period obtained a V / C ratio of 0.45 level C, the operational period with a V / C ratio of 0.45 level C, and after 5 years of operation the V / C ratio is 0.58 level C which means that the flow is stable, but the operating speed begins to be limited based on the level of service (LOS) table. Parking needs based on the building area of 2832 m2 were obtained as many as 113 srp, while based on the available parking area it can accommodate as many as 121 srp, so the parking space requirements of the Padang Eye Center Special Eye Hospital have been met. The alternative solution to this analysis is the placement of regulatory officers in front of the entrance and exit of the Khatib Sulaiman Road intersection during the construction period, regulating parking circulation within the hospital area, and making barrier gates to regulate vehicle traffic flow.